2018
DOI: 10.1016/j.soard.2018.01.021
|View full text |Cite
|
Sign up to set email alerts
|

Is preoperative gastroscopy necessary before sleeve gastrectomy and Roux-en-Y gastric bypass?

Abstract: Preoperative EGD is indicated before SG but not before RYGB for asymptomatic patients without a risk for gastric pathology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 22 publications
0
15
0
1
Order By: Relevance
“…Schatzki ring or stricture was noted in 0.5% to 3.0% of patients in the literature. 8,13,24 Strictures may have more serious implications and should be evaluated prior to surgery to rule out underlying malignancy. It can also be seen as a marker of severity of reflux prompting avoidance of SG.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Schatzki ring or stricture was noted in 0.5% to 3.0% of patients in the literature. 8,13,24 Strictures may have more serious implications and should be evaluated prior to surgery to rule out underlying malignancy. It can also be seen as a marker of severity of reflux prompting avoidance of SG.…”
Section: Discussionmentioning
confidence: 99%
“…Barrett's esophagus or intestinal metaplasia was noted in 3.1% of our patients with a prevalence of 0.2% to 3.1% in the literature. 8,10,14,24 Although this diagnosis is not prominent, it may lead to a delay in surgery, medical treatment, repeat EGD procedures, or change in procedure choice. At the most recent international consensus conference on sleeve gastrectomy, 94.5% of experts agreed that Barrett's esophagus is a major contraindication to the performance of SG.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ASMBS guidelines advocates the use of UGIE preoperatively on a selective basis based on the presence of symptoms [16]. This is in contrast to the observation by another study that found significant findings relevant for SG (hiatus hernia, esophagitis, Barrett's esophagus, esophageal dysplasia) in 23% patients, of whom only half were symptomatic and the authors concluded that preoperative UGIE was indicated before SG for all patients irrespective of symptoms [17]. Once again, significant variation was observed in this survey with only 65% surgeons advocating routine UGIE before SG.…”
Section: Discussionmentioning
confidence: 83%
“…Saarinen et al[7] concluded that a pre-operative OGDF is recommended before a SG, but it is not mandatory before a RYGB for asymptomatic patients without any risk factor for gastric pathology (family history of gastric cancer, H. pylori infection, nonsteroidal antiinflammatory drugs usage, tabagism, age > to 50 years, kidneys, heart or lungs chronic diseases). The American Society for Gastrointestinal Endoscopy and the American Society for Metabolic and Bariatric Surgery defined some guidelines rooted from evidence-based medicine[8].…”
Section: Pre-operative Oeso-gastroduodenal Fibroscopymentioning
confidence: 99%